2021
DOI: 10.23919/jcn.2021.000016
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum sensing for cognitive radio network with multiple receive antennas under impulsive noise environments

Abstract: Article that has been accepted for inclusion in a future issue of a journal. Content is final as presented, with the exception of pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…A distribuição SαS é amplamente utilizada na modelagem do ruído impulsivo nos artigos mais recentes que analisam o desempenho do sensoriamento espectral em redes de rádios cognitivos. Citam-se [9]- [14] como exemplos.…”
Section: B Trabalhos Relacionados E Estrutura Do Artigounclassified
“…A distribuição SαS é amplamente utilizada na modelagem do ruído impulsivo nos artigos mais recentes que analisam o desempenho do sensoriamento espectral em redes de rádios cognitivos. Citam-se [9]- [14] como exemplos.…”
Section: B Trabalhos Relacionados E Estrutura Do Artigounclassified
“…It has been found that the SαS distribution is widely used in impulsive noise modeling in the most recent articles that analyze the performance of spectrum sensing in cognitive radio networks. References [20]- [25] are cited as examples. In [17], the adequacy of the SαS distribution is analyzed in contrast to the αSG distribution with non-zero temporal correlation, in the context of underwater spectrum sensing subjected to snapping shrimp noise.…”
Section: A Related Researchmentioning
confidence: 99%
“…Various methods have been proposed by the researchers. Energy detection, cyclostationary feature detection, and matched filter [22] are the most commonly used methods of spectrum sensing. The probability of detection (P d ) and probability of false alarm (P f ) are among the important parameters used in spectrum sensing.…”
Section: Introductionmentioning
confidence: 99%